Extensive Reading in EFL Learners: Moving from Theory to Practices - Rini Lindawati (International Journal of English and Applied Linguistics (IJEAL), 2021)
Since its introduction to the subject of English Foreign Language, extensive reading has grown in popularity (EFL). This type of reading has been shown to provide EFL learners with numerous benefits in a variety of areas. Extensive Reading has also been done in a number of situations. This essay seeks to (1) provide a thorough understanding of ER, both theoretically and in terms of principles, and (2) summarize recent ER research in EFL settings. The method of library research was employed by the researcher. According to the reports, extensive reading increased reading comprehension, vocabulary understanding, and writing abilities. Furthermore, the students showed positive attitudes and perceptions of extensive reading in EFL contexts. More teachers and practitioners are hoped for. Furthermore, the students had positive attitudes and impressions of extensive reading in EFL contexts. It is hoped that more teachers, practitioners, and educational institutions would see the possibility of incorporating Extensive Reading into the English curriculum in order to benefit from its multiple benefits.